2021
DOI: 10.3390/v13050769
|View full text |Cite
|
Sign up to set email alerts
|

N-Linked Glycosylation on Anthrax Toxin Receptor 1 Is Essential for Seneca Valley Virus Infection

Abstract: Seneca Valley virus (SVV) is a picornavirus with potency in selectively infecting and lysing cancerous cells. The cellular receptor for SVV mediating the selective tropism for tumors is anthrax toxin receptor 1 (ANTXR1), a type I transmembrane protein expressed in tumors. Similar to other mammalian receptors, ANTXR1 has been shown to harbor N-linked glycosylation sites in its extracellular vWA domain. However, the exact role of ANTXR1 glycosylation on SVV attachment and cellular entry was unknown. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…Glycosylation in viral proteins or receptors is a highly regulated posttranslational modification, which has multiple effects on viral structure, function, signaling pathways and so on. N-linked glycosylation on anthrax toxin receptor 1 has been recently demonstrated to be essential for SVA infection (Jayawardena et al, 2021). At least four sugar-related metabolites, namely UDP-d-glucuronic acid, uridine-5'-diphosphogalactose disodium salt, luteolin 4'-Oglucoside and oleandrin, were identified here as significantly differential ones between SVA-and non-infected groups in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…Glycosylation in viral proteins or receptors is a highly regulated posttranslational modification, which has multiple effects on viral structure, function, signaling pathways and so on. N-linked glycosylation on anthrax toxin receptor 1 has been recently demonstrated to be essential for SVA infection (Jayawardena et al, 2021). At least four sugar-related metabolites, namely UDP-d-glucuronic acid, uridine-5'-diphosphogalactose disodium salt, luteolin 4'-Oglucoside and oleandrin, were identified here as significantly differential ones between SVA-and non-infected groups in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…Therefore, it is possible that mutation of some of these key amino acids could block SVA without disrupting collagen binding. Furthermore, N-linked glycosylation of specific ANTXR1 residues has recently been shown to be critical for SVA entry into human cells 33 , thus revealing new targets for potentially blocking SVA infection without interfering with the normal physiological function of ANTXR1.…”
Section: Discussionmentioning
confidence: 99%
“…Again, this group confirmed the association with SCLC-N, when they evaluated neurogenic transcription factors in responders and non-responders and also found that the elevated NEUROD1 and low ASCL1, markers of SCLC-N, were associated with downregulation of antiviral IFN gene signaling (Miles et al, 2017). The same group also established that glycosylation of the TEM8/ANTXR1 receptor was necessary for SVV-001 binding, cell entry, and infection (Jayawardena et al, 2021). Although this association was identified in SCLC, it is likely, given TEM8/ANTXR1 is the receptor for SVV-001, that SVV-001 permissive subtypes of other neuroendocrine cancers share similar features to SCLC-N, including elevated TEM8/ANTXR1 and low expression of IFN genes.…”
Section: Study Description Outcomesmentioning
confidence: 95%